2016
DOI: 10.1002/zaac.201600380
|View full text |Cite
|
Sign up to set email alerts
|

Ionic‐Liquid‐Based Synthesis of the Germanium‐Iron Carbonyls FeI4{GeI3Fe(CO)3}2 and (GeI3)2Fe(CO)4

Abstract: Dark red and brick red transparent crystals of FeI4{GeI3Fe(CO)3}2 (1) and (GeI3)2Fe(CO)4 (2) were obtained by reacting GeI4 and Fe2(CO)9 or Fe3(CO)12 in a mixture of [BMIM]Cl and AlCl3 as ionic liquid (BMIm = 1‐butyl‐3‐methylimidazolium). According to X‐ray structure analysis based on single crystals, the title compounds exhibit cluster units with Fe–Ge bonds. FeI4{GeI3Fe(CO)3}2 consists of two GeI2I1/2‐Fe(CO)3I2/2 units that are interlinked by a distorted octahedral FeI6/2 group. (GeI3)2Fe(CO)4 consists of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(38 citation statements)
references
References 20 publications
3
35
0
Order By: Relevance
“…After approximately two weeks, bright‐red needles of the already known compound Fe(CO) 4 {GeI 3 } 2 ( I ) were formed. This finding is not surprising since Fe(CO) 4 {GeI 3 } 2 was also directly formed in absence of Ph 3 GeCl [12] . 1 crystallizes in the monoclinic space group P2 1 /c and contains [BMIm] + cations and [(FeI 2 ) 0.75 {Fe(CO) 2 I(GeI 3 ) 2 } 2 ] 2− anions (Table 1, Figure 2).…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…After approximately two weeks, bright‐red needles of the already known compound Fe(CO) 4 {GeI 3 } 2 ( I ) were formed. This finding is not surprising since Fe(CO) 4 {GeI 3 } 2 was also directly formed in absence of Ph 3 GeCl [12] . 1 crystallizes in the monoclinic space group P2 1 /c and contains [BMIm] + cations and [(FeI 2 ) 0.75 {Fe(CO) 2 I(GeI 3 ) 2 } 2 ] 2− anions (Table 1, Figure 2).…”
Section: Resultsmentioning
confidence: 74%
“…First of all, a decisive parameter to influence the realization of a specific carbonyl cluster compound in the Ge−Fe system relates to the type, and especially, to the Lewis acidity of the IL (Figure 4). Already for the previously reported compounds, we have observed that (GeI 3 ) 2 Fe(CO) 4 ( I ) was obtained with a 1 : 1 mixture of [BMIm]Cl/AlCl 3 [12] . Upon increasing the amount of AlCl 3 to a 1 : 2 a mixture of [BMIm]Cl/AlCl 3 , GeI 3 Fe(CO) 3 } 2 FeI 4 ( II ) was formed [12] .…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Besides application in classic solid state chemistry, ILs can be used as reaction media to prepare (oligomeric) metal complexes, metal organic frameworks, coordination polymers [25–35] or cluster compounds incorporating main group elements [36–41] . Within SPP 1708, the synthesis of intermetallic cluster and nanoparticles, [3,42–56] the controlled synthesis of polyanions and cations, [57–61] solvent‐free chalcogenidometal‐containing materials, [62–75] deposition of nanocrystalline materials, [76–80] ionic liquids as precursors for inorganic materials, [81–83] ionic‐liquid‐modified hybrid materials, [84–87] as well as the low‐temperature synthesis of thermoelectric materials [88–92] were investigated. Moreover, theoretical [93–106] and solubility [107–114] aspects during the synthesis process were studied.…”
Section: Introductionmentioning
confidence: 99%